Microbial ecology and genetics of benzalkonium chloride biotransformation in the environment - Ertekin, Emine. (Thesis (Ph.D.) - Bogazici University. Institute of Environmental Sciences, 2017., 2017)
Contamination of the environment with biocides such as quaternary ammonium compounds (QACs) has been associated with many public health and environmental hazards such as proliferation of antimicrobial resistance and ecotoxicity. The biodegradation of benzalkonium chloride (BAC), the most commonly used type of QAC biocides, is initiated with the conversion of BAC to benzyldimethyl amine (BDMA) via an N-dealkylation reaction. This reaction removes the biocidal activity of the BAC thus eliminates its impact in the environment. Although BAC N-dealkylation is the major bioreaction that detoxifies the QACs in the environment, structure of BAC degrading microbial communities are not fully understood. In addition, BAC degrading microorganisms along with the genes underlying the BAC degradation pathway remain poorly elucidated. In this study, the common structure of BAC degrading enrichment communities originating from different environments has been characterized. A novel species named Pseudomonas sp. BIOMIG1, which degrades BACs, was predominant in all of these communities. Whole genomes of four BIOMIG1 phenotypes differ from each other with respect to the steps achieved in BAC degradation pathway, i.e., a complete BAC degrader, a BDMA accumulator, a BDMA degrader and a non degrader, were sequenced and compared. The results revealed that a gene cluster specific to the former two strains was likely involved in converting BAC to BDMA, which is the key step in the pathway. This gene cluster consisted of genes encoding two major facilitator superfamily (MFS) type transport proteins, a transcriptional regulator, a Rieske oxygenase, a sterol binding protein, two hypothetical proteins, and an integrase. The identified Rieske oxygenase was the only catabolic gene that was homologous to those transforming QAC-like compounds. Nonetheless this enzyme had low sequence identity (~30% amino acid identity) to its closest biochemically characterized relatives and was named oxyBAC. E. coli transformed with oxyBAC could transform BAC into equimolar amounts of BDMA, confirming its function as a novel enzyme catalyzing an unusual dealkylation reaction.
Keywords: Benzalkonium chloride.